Sustainable Data-Driven Strategies and Active Well-Being: A Case Study - Giuseppe Mincolelli; Gian Andrea Giacobone; Michele Marchi (DIID, 2024)
Nowadays the world is characterized by an increasingly aging society. This phenomenon represents a risk for the sustainability of the healthcare system. One of the factors that can accelerate the consequences of the aging process is sedentary behavior. Currently, there is a large availability of wearable smart devices and mobile applications, that can collect data. However, some social and functional problems were observed, therefore we believe that there is great room for improvement (Mincolelli et al., 2018). In addition, the paradigm of the Internet of Things is enabling those applications to share data with other programs and smart devices, which, in turn, can generate an ecosystem of services that can improve the quality of life, not only of the single user, but of many groups of a determined social context. The contribution presents a case study (PLEINAIR project) that focuses specifically on the development of Human-Centered outdoor smart technologies that can adapt themselves to the necessities of people of all ages and abilities in order to encourage them of taking care of their health.